PENGARUH MODEL PEMBELAJARAN TPACK MELALUI MEDIA YOUTUBE TERHADAP KEMAMPUAN BERBICARA TEKS ANEKDOT PADA SISWA KELAS X SMA NEGERI 1 SEI BALAI T.A 2025/2026 - Silvia Silvia; Hanina Hanina (STKIP Pesisir Selatan, 2026)
The study aims to determine the effect of the TPACK learning model through YouTube on the ability to speak anecdotal texts at Xth grade students of SMA Negeri 1 Sei Balai in 2025/2026 Academic Year. The problem in this study is the students' low ability to speak anecdotal texts, particularly in understanding the content and appropriateness of anecdotal texts, the structure of anecdotal texts, and the use of appropriate linguistic rules. This type of research used a quantitative research with an experimental method using a posttest-only control group design. The results showed that the experimental class's anecdotal speaking ability was better than the control class's. The control class's average score was 68.33, categorized as good, while the experimental class's average score was 79, categorized as good. Based on the results of the hypothesis test using the t-test, it was found that (t_count > t_table), i.e., 5.99 > 1.67. Thus, the null hypothesis (H₀) stating there is no significant effect is rejected, and the alternative hypothesis (Hₐ) stating a significant effect of using the TPACK learning model through YouTube on the anecdotal speaking ability at Xth students of SMA Negeri 1 Sei Balai in the 2025/2026 Academic Year is accepted.